Dissonance on perceptions of end‐of‐life needs between health‐care providers and members of the public: Quantitative cross‐sectional surveys. (13th March 2019) - Cardona, Magnolia; Lewis, Ebony; Shanmugam, Shantiban; Nicholson, Margaret; Williamson, Margaret; Hanly, Laura; Hillman, Ken
Abstract : Objective: To investigate views, determinants and barriers to end‐of‐life discussions for doctors, nurses and members of the public (MoP) and their acceptability of risk prediction tools. Methods: Concurrent surveys of 360 doctors and nurses and 497 MoP. Results: Sixty per cent of clinicians reported high confidence in initiating end‐of‐life discussions, and 55.8% regularly engaged in them. Barriers to end‐of‐life communication reported by clinicians were uncertainty on the likely time to death (44.7%) and family requests to withhold information from patients (44.2%). By contrast, most (92.8%) MoP wanted information about life expectancy; 89.9% wanted involvement in treatment decisions if the likelihood of death was high; and 23.8% already had an advance care directive. Conclusions: A dissonance exists between doctor/nurses perception of older peoples' preference for receiving prognostic information and the public desire for involvement in decision‐making at the end of life. As public attitudes change, strategies for greater involvement of patients in shared end‐of‐life planning are warranted.